Determinants of physician attitudes towards the new selective measles vaccine mandate in Germany - Julia Neufeind; Cornelia Betsch; Vera Zylka-Menhorn; Ole Wichmann (BMC, 2021)
Abstract Background In Germany, a mandatory policy on measles vaccination came into effect in March 2020. Physicians, as the main vaccine providers, have a crucial role in implementing it. Mandatory vaccination changes the preconditions under which patient-provider communication on vaccines occurs. Physicians might or might not favor vaccine mandates depending on, among other factors, their attitudes towards vaccines and capabilities as vaccine providers. The aim of this study was to investigate in different subgroups of physicians the association between various factors and their attitudes towards a mandatory policy. Methods In total, 2229 physicians participated in a mixed-mode online/paper-pencil survey. Respondents were general practitioners, pediatricians, gynecologists, and internists. Primary determinants were the 5C psychological antecedents of vaccination, communication self-efficacy, patient clientele, projected consequences of the mandate and sociodemographic characteristics. Associations between outcomes and determinants were examined using linear regression analysis. Results Approximately 86% of physicians were in favor of the measles vaccine mandate for children. Regarding the 5C model, physicians were more in favor of vaccine mandates when they scored higher on confidence and collective responsibility, and lower on complacency and calculation. They were more in favor of vaccine mandates when they had higher communication self-efficacy and a more vaccine-positive patient clientele. Pediatricians were less in favor of mandates for children (80.0%) than other physician subgroups (87.1%). They were also less convinced that a mandate would result in more children getting vaccinated (59.3%) than other physician subgroups (78.3%). When controlled for these expected consequences, being a pediatrician no longer lowered the attitude towards the mandate. Conclusions Physicians in Germany are predominantly in favor of a measles vaccine mandate. Whether or not physicians believe the mandate to be effective in increasing vaccine coverage affects their attitude towards the mandate. In pediatricians, this belief explains their less positive attitude towards the mandate. In addition, physicians need adequate support to communicate well with patients, especially those who are hesitant, to booster their communication self-efficacy. To increase acceptance of vaccine mandates, the 5C model can be used, e.g., collective responsibility can be communicated, to avoid anger stemming from a negative attitude to mandates.